2019
DOI: 10.1111/wej.12531
|View full text |Cite
|
Sign up to set email alerts
|

Removal processes of indicator organisms and opportunistic pathogens in an anaerobic digester‐constructed wetland system

Abstract: Factors affecting the removal of opportunistic pathogens were evaluated in a hybrid constructed wetland (CW 2) treating rural wastewater. The correlations between the bacterial population and the environmental variables showed that bacteria discharge was the result of abiotic factors change such as temperature (T), electrical conductivity (EC), dissolved oxygen (DO), organic matter and nutrient availability, as well as biotic factors like antagonism and competition with the native microbial community. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The highest removal efficiency reported for TC, FC, intestinal nematode parasites eggs, and protozoan cysts was 99.999% (5 logs), 99.99% (4 logs), 99%, and 99%, respectively (Darvishmotevallia, Moradniab, Asgaric, Noorisepehrd, & Mohammadif, 2019). Similarly, another hybrid CW system (CWs in series with anaerobic digester) reported the bacterial removal efficiency of more than 98% (Khouja, M’Hiri, Ouzari, & Saidi, 2019). Combined overflow sewer was treated in CWs for 7–10 years and reported that the indicator microorganisms E. coli (1.1/0.8 log10), intestinal enterococci (1.3/0.8 log10), and somatic coliphages (0.6/1.0 log10) showed comparably low process variations (Tondera, Ruppelt, Pinnekamp, Kistemann, & Schreiber, 2019).…”
Section: Wetlands For Pathogens and Virus Removalmentioning
confidence: 99%
“…The highest removal efficiency reported for TC, FC, intestinal nematode parasites eggs, and protozoan cysts was 99.999% (5 logs), 99.99% (4 logs), 99%, and 99%, respectively (Darvishmotevallia, Moradniab, Asgaric, Noorisepehrd, & Mohammadif, 2019). Similarly, another hybrid CW system (CWs in series with anaerobic digester) reported the bacterial removal efficiency of more than 98% (Khouja, M’Hiri, Ouzari, & Saidi, 2019). Combined overflow sewer was treated in CWs for 7–10 years and reported that the indicator microorganisms E. coli (1.1/0.8 log10), intestinal enterococci (1.3/0.8 log10), and somatic coliphages (0.6/1.0 log10) showed comparably low process variations (Tondera, Ruppelt, Pinnekamp, Kistemann, & Schreiber, 2019).…”
Section: Wetlands For Pathogens and Virus Removalmentioning
confidence: 99%
“…In Tunisia, the use of constructed wetlands dates back to the early 2000s, yet to date this treatment technology has only been reported for a handful of laboratory experiments, and pilot and large-scale systems (Keffala and Ghrabi 2005 ; Ghrabi et al 2011 ; Khouja et al 2019 ). However, the assessment of wetland performance is often limited to monitoring water quality and pollutant removal efficiency.…”
Section: Introductionmentioning
confidence: 99%